Synthesis, structures and magnetic properties of dysprosium(iii) complexes based on amino-bis(benzotriazole phenolate) and nitrophenolates: influence over the slow relaxation of the magnetization. Issue 47 (8th November 2021) - Chen, Bo-Yi; Tsai, Min-Yem; Su, Yu-Chia; Lin, Po-Heng; Long, Jérôme
Abstract : Field-induced slow relaxation in dysprosium amino-bis(benzotriazole) phenolate complexes. Abstract : We report the synthesis and crystal structures of four dysprosium(iii ) complexes based on the amino-bis(benzotriazole phenolate) ligand ( C1NN BiBTP-H2 ). While a pentagonal bipyramid complex [Dy( C1NN BiBTP-H)Cl2 DMF]·THF (1 ·THF) is obtained in the absence of co-ligands, the association with nitrophenolate derivatives bearing a distinct number and position of nitro groups affords a series of octacoordinated complexes of formulas [Dy( C1NN BiBTP)L 1 (MeOH)2 ] (2 ), [Dy( C1NN BiBTP)L 2 (MeOH)2 ] (3 ) and [Dy( C1NN BiBTP)L 3 (MeOH)2 ] (4 ) (HL 1 = 2, 4-dinitrophenol; HL 2 = 2, 4, 6-trinitrophenol; HL 3 = 2, 5-dinitrophenol). Investigations of the magnetic properties reveal that all the complexes exhibit a field-induced slow relaxation of the magnetization, mainly driven by a Raman relaxation. The observed distinct dynamics could be ascribed to the substituents' influence of the nitrophenolate that affects the Dy–O(phenoxide) distance.